Perbedaan Gangguan Emosional Dan Beban Kardiovaskuler Pada Tenaga Kerja Yang Terpapar Kebisingan Di Atas Dan Di Bawah Nilai Ambang Batas Di Pt. Iskandar Indah Printing Textile Surakarta - PRABAWATI, Fitri, Tarwaka, PGDip Sc, M.Erg, Kusuma Estu Werdani, SKM., M.Kes (2016)
Noise not only can cause hearing loss, but also may interfere in emotional disorders and cardiovascular disorders that is caused by work load. The purposed of this research is to knowed the differences of emotional disorders and cardiovacular load on employee that noise expused above dan below of the threshold value at PT. Iskandar Indah Printing Textile Surakarta. This research was conducted used a observational methods with cross-sectional approach. Population research is employees part of weaving is 40 employees, part of printing is 20 employees and part of riching is 20 employees. The selection of sample with purposive sampling method as many as 26 employees of weaving part, 13 employees of printing part and 13 employees in riching part. Statistical test of emotional disorders and cardiovascular load using mann whitney u-test. The result showed that there are differences of emotional disorders on employees that noise expused above and below of the threshold value at PT. Iskandar Indah Printing Textile Surakarta with significant value p-value = .000 or p-value = ≤0.05 and there are differences cardiovascular load on employees that noise expused above and below of threshold value at PT. Iskandar Indah Printing Textile Surakarta with significant value p-value = .000 or p-value = ≤0.05. Based on this research, the use of protective equipment standard ear can prevent the onset of emotional disorders and cardiovascular load.